CAPITAL STRUCTURE CATALYST: CONNECTING FINANCIAL LITERACY, INNOVATION, PROFITABILITY FOR VENTURE GROWTH - Andarwati; Nanang Suryadi; Rizka Zulfikar (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study investigated the impact of financial literacy, innovation, and profitability on the performance of new ventures, focusing on the mediating role of capital structure. Addressing a sample of 287 new ventures in East Java, Indonesia, this study employed the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to analyze the relationships among key constructs. The findings revealed that innovation and profitability significantly influenced capital structure, which had a strong positive effect on firm performance.  The innovation had a direct impact on performance, while financial literacy and profitability did not show significant direct effects. Among the indirect effects, only innovation had a significant impact on performance through capital structure, reinforcing its strategic importance. The results of this study suggest that innovation, more than financial acumen or short-term profitability, plays a central role in shaping financial strategies that enhance new venture outcomes. The findings contributed to the entrepreneurial and financial management literature by integrating financial and non-financial competencies into a comprehensive model of entrepreneurial and financial management. This study also provided policymakers, educators, and practitioners with practical insights on how to strengthen the sustainability of new ventures through targeted innovation support and strategic financial structuring.